A construção da intersubjetividade: reflexões identitárias acerca da relação professor-aluno sob o prisma psicanalítico - Zoppi, Pedro Colombaroli [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
The present work intends to situate in a psychoanalytical way the relationship between teacher and student in the human sphere. For such a purpose, two data sources will be compared and mixed up, so to say: empirical data collected from school students and teachers; and a theoretical-figurative model concerning questions we focused on, as well. As a result, very important reflexions and statements on the problem are expected to be made, therefore enriching the teaching practice

O presente trabalho intenta situar a relação professor-aluno na esfera do humano, munindo-se de dados empíricos coletados de alunos e professores de sexto ano do ensino fundamental, bem como de um modelo teórico-figurativo de esteio psicanalítico, no afã de elaborar uma teia de reflexões que enriqueçam a prática docente
Keywords: Educação; Aprendizagem; Relações humanas; Docência; Human relationships; Education; Teaching; Learning